Superovulation in Gir cross breds using follicle stimulating hormone - DEOPURKAR, V L; NAIK, V S; RAJ, B B; GULAVANE, S U; CHAUBAL, S A; JADHAV, P D (The Indian Journal of Animal Reproduction, 2003)
Seven Cir Cross bred Cows were treated with Follicle stimulating Hormome (Folltropin, Veterpharma Inc., Canada) at a descending dose rate, over a period of four days. The superovulatory response was assesed by per-rectal palpation of ovaries and embryos recovered. The embryos were collected non-surgically and graded as viable and non viable. The average number of Corpora Lu tea per animal were 10±2 while the unovulatory follicle were 1.5 per animal. The total number of embryos recovered from seven donors were forty one. The overall percentage of viable embryos recovered were 39.02% (16/ 41). The overall percentage of morulla and blastocysts recovered were 43.90% (18/ 41) and 17.07% (7 / 41) respectively. On an average the embryo yield per donor was 5.85 out of these 3.57 embryos were viable and transferable.